Speaking Skill in Correlation with English Speaking Learning Habit and Self Confidence of Vocational High School Students - Mega, Iful Rahmawati; Sugiarto, Dody (Journal of Foreign Language Teaching and Learning, 2020)
The purpose of conducting this study is based on problem identification asking whether there are correlations among English speaking learning habits and self-confidence toward English speaking skills in promoting local tourism and culture of Bangka Belitung. The first-grade students of SMKN 3 Pangkalpinang in the academic year of 2018/2019 majoring in Tourism Travel Business Agent became the population in this study, and it took 50 students as the sample using a purposive random sampling technique. This correlational study used questionnaires and oral tests in collecting the data. The oral test was used to obtain English speaking skill data, while the questionnaires were used to obtain English speaking learning habits and students’ self-confidence data. The data were then analyzed using Simple and Multiple Correlation and Regression. The results of this study revealed that (1) there was a relationship between English speaking learning habit and English speaking skill, (2) there was a correlation between students’ self-confidence and English speaking skill, and (3) English speaking learning habit, confidence, and English speaking skill was simultaneously and positively correlated. In short, this study leads to a recommendation to the teachers and students to be aware of having good English speaking learning habits and high self-confidence to enhance English speaking skills.